2019
DOI: 10.3389/fnins.2019.00709
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Grained Parcellation of the Macaque Nucleus Accumbens by High-Resolution Diffusion Tensor Tractography

Abstract: Limited in part by the spatial resolution of typical in vivo magnetic resonance imaging (MRI) data, recent neuroimaging studies have only identified a connectivity-based shell-core-like partitioning of the nucleus accumbens (Acb) in humans. This has hindered the process of making a more refined description of the Acb using non-invasive neuroimaging technologies and approaches. In this study, high-resolution ex vivo macaque brain diffusion MRI data were acquired to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 91 publications
(136 reference statements)
2
14
0
Order By: Relevance
“…Our medial-lateral subdivision of the VS is in line with recent macaque ex vivo highresolution diffusion tensor MRI findings (42), which demonstrated that the VS contains medial, lateral, ventral, and dorsal subdivisions. Whereas the medial tractography-based subdivision corresponds well to the histological NAcc, the lateral tractographybased VS region corresponds to the histological "neurochemically unique domains of the accumbens and putamen (NUDAPs)," which show a unique pattern of u-and k-opioid as well as D1-like dopamine receptors (42). This tractography-based medial-lateral distinction in the macaque matches our fMRI activations, suggesting a lateral VS-NAcc subdivision in humans.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our medial-lateral subdivision of the VS is in line with recent macaque ex vivo highresolution diffusion tensor MRI findings (42), which demonstrated that the VS contains medial, lateral, ventral, and dorsal subdivisions. Whereas the medial tractography-based subdivision corresponds well to the histological NAcc, the lateral tractographybased VS region corresponds to the histological "neurochemically unique domains of the accumbens and putamen (NUDAPs)," which show a unique pattern of u-and k-opioid as well as D1-like dopamine receptors (42). This tractography-based medial-lateral distinction in the macaque matches our fMRI activations, suggesting a lateral VS-NAcc subdivision in humans.…”
Section: Discussionsupporting
confidence: 89%
“…Anatomically, the VS is heterogeneous, with differences between subregions such as the core and shell (12), and different activation patterns depending on which limbic and cortical inputs are integrated in different contexts (5). Our medial-lateral subdivision of the VS is in line with recent macaque ex vivo highresolution diffusion tensor MRI findings (42), which demonstrated that the VS contains medial, lateral, ventral, and dorsal subdivisions. Whereas the medial tractography-based subdivision corresponds well to the histological NAcc, the lateral tractographybased VS region corresponds to the histological "neurochemically unique domains of the accumbens and putamen (NUDAPs)," which show a unique pattern of u-and k-opioid as well as D1-like dopamine receptors (42).…”
Section: Discussionsupporting
confidence: 85%
“…Second, to some extent, challenges were raised in CBP studies because of the inter-individual variability, which made it difficult to relate the anatomical connectivity patterns of a region to its functional roles [29]. Third, in this study, the efficiency of the parcellation framework based on CBP and the parameters for parcellation have been validated by many studies [33,43,48,92]. In general, it is worth noting that all the parameters must be reasonable, which means that they cannot be uncommon extreme values, otherwise wrong results will be tracked.…”
Section: Discussionmentioning
confidence: 89%
“…However, in the current study, we mainly set two parameters (number of samples = 15000; step size = 0.2 mm), other parameters are based on the default values. All these parameters were based on previous studies [33,42] and the official instructions of FSL. Tournier et al have revealed that the dispersion in tractography is dependent on the step size; small step sizes reduce the spread of probabilistic tracking results [98].…”
Section: Discussionmentioning
confidence: 99%
“…3A) and low-resolution in vivo (Fig. 3B) macaque MRI datasets showed that the Acb can be subdivided into ventromedial and dorsolateral regions based on whole-brain voxel-wise tractography (Xia et al, 2019b).…”
Section: Tractography-defined Seedsmentioning
confidence: 99%